Effect and mechanism of action of isosorbide-5-mononitrate. Issue 6 (June 1988) - Hayes, P C; Westaby, D; Williams, R
Abstract : Nitrates have been shown to decrease portal pressure in cirrhotic patients with portal hypertension and this has been attributed to decreased portal venous resistance. We studied the effect and mechanism of action of oral administration of isosorbide-5-mononitrate (Is-5-Mn) (20 mg), which, unlike the dinitrate, does not require hepatic biotransformation to a vasoactive metabolite on portal and systemic haemodynamics in 11 patients with portal hypertension complicating cirrhosis. A significant reduction in portal pressure gradient (WHVP-FHVP) (from 23.9 (3.4) to 21.8 (3.4) mmHg: p less than 0.005) occurred 60 minutes after Is-5-Mn due entirely to a fall in WHVP, associated with decreased estimated liver blood flow (from 1940 (159) to 1639 (179) ml/min: p less than 0.05). Right atrial and pulmonary artery pressures and cardiac index fell significantly whilst mean arterial pressure remained unaffected. Heart rate and the calculated systemic vascular resistance index increased significantly. Significant correlations existed between the reduction in portal pressure gradient and fall in cardiac index (r = 0.65, p less than 0.05) and increase in systemic vascular resistance index (r = 0.72, p less than 0.02). The observed decrease in estimated liver blood flow, in association with an increase in systemic vascular resistance index, suggests that baroreceptor mediated splanchnic vasoconstriction may be one of the factors responsible for the fall in portal pressure, rather than portal venous dilatation.